PENGARUH PENDAPATAN ASLI DAERAH TERHADAP BELANJA MODAL PADA KOTA/KABUPATEN DI PROVINSI JAWA BARAT - Arethusa, Tasya Amanda; Terawati, Mira Teram (Publika Citra Media, 2025)
Regional autonomy aims to improve equitable development, people's welfare, and public services. The government as a public service provider has the task of managing funds obtained from the community to improve public service facilities through capital expenditure allocation. This study aims to determine the influence of Local Own-source Revenue on Capital Expenditure on Cities and Regencies in West Java Province for the 2021-2022 period. The method of this research is descriptive and verification with a quantitative approach. The data source used in this study is secondary data obtained from the official website of the Central Statistics Agency of West Java Province. The population in this study is 9 cities and 18 regencies in West Java Province. The data analysis techniques used in this study are simple linear regression analysis. The study results show that Local Own-source Revenue has an effect on Capital Expenditure.